2000
DOI: 10.1152/ajpregu.2000.279.3.r860
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral artery sarcoplasmic reticulum Ca2+stores and contractility: changes with development

Abstract: To test the hypothesis that sarcoplasmic reticulum (SR) Ca(2+) stores play a key role in norepinephrine (NE)-induced contraction of fetal and adult cerebral arteries and that Ca(2+) stores change with development, we performed the following study. In main branch middle cerebral arteries (MCA) from near-term fetal ( approximately 140 days) and nonpregnant adult sheep, we measured NE-induced contraction and intracellular Ca(2+) concentration ([Ca(2+)](i)) in the absence and presence of different blockers. In adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 43 publications
2
69
0
Order By: Relevance
“…These data indicate that the pressure-induced arterial wall [Ca 2ϩ ] i elevation and constriction is not due to, but instead opposed by, SR Ca 2ϩ release. Consistent with this notion is evidence that in ovine fetal cerebral arteries norepinephrineinduced contractions occur primarily due to Ca 2ϩ influx, whereas in adults Ca 2ϩ released from intracellular stores also contributes (35). Whether, in addition to depolarization, mechanosensitive elements directly signal pressure-induced voltagedependent Ca 2ϩ channel activation in the newborn cerebrovasculature cannot be concluded from our study (21,36).…”
Section: Pressure-induced Constriction Occurs Via Voltage-dependent Cmentioning
confidence: 50%
See 1 more Smart Citation
“…These data indicate that the pressure-induced arterial wall [Ca 2ϩ ] i elevation and constriction is not due to, but instead opposed by, SR Ca 2ϩ release. Consistent with this notion is evidence that in ovine fetal cerebral arteries norepinephrineinduced contractions occur primarily due to Ca 2ϩ influx, whereas in adults Ca 2ϩ released from intracellular stores also contributes (35). Whether, in addition to depolarization, mechanosensitive elements directly signal pressure-induced voltagedependent Ca 2ϩ channel activation in the newborn cerebrovasculature cannot be concluded from our study (21,36).…”
Section: Pressure-induced Constriction Occurs Via Voltage-dependent Cmentioning
confidence: 50%
“…Disorders of the newborn cerebral circulation, in particular, are a predominant cause of mortality and can result in life-long disabilities in survivors. Recent studies have indicated that the newborn and adult vasculature show important physiological differences, including those relating to resting membrane potential (14), voltage-dependent Ca 2ϩ channels (7), intracellular Ca 2ϩ dynamics (35), localized intracellular Ca 2ϩ release events (17), and cGMP sensitivity (37). A functional myogenic response is known to be present at the newborn stage of development and appears to involve the activation of voltagedependent Ca 2ϩ channels (17).…”
mentioning
confidence: 99%
“…For many vessels, including cerebral arteries (51,55), calcium entry through L-type Ca 2ϩ channels constitutes the main fraction of contractile calcium, owing to sparse or poorly developed sarcoplasmic reticulum. This is particularly true for immature cerebral arteries, which are essentially totally dependent on Ca 2ϩ influx through L-type Ca 2ϩ channels for contraction (1,41,44).…”
Section: Electromechanical Couplingmentioning
confidence: 99%
“…Recent studies have indicated that physiological regulation of the newborn vasculature is very different when compared with that of the adult. When considering the physiological functions of vascular smooth muscle, several age-related differences have been described, including those relating to resting membrane potential (8), voltage-dependent Ca 2ϩ channels (2), intracellular Ca 2ϩ dynamics (29), localized intracellular Ca 2ϩ release events (14), and sensitivity to cGMP (33). Thus signal transduction mechanisms characterized in the adult circulation may not extrapolate to the newborn.…”
mentioning
confidence: 99%